Photocatalysis: Novel Porous Boron Nitride Nanosheet with Carbon Doping: Potential Metal‐Free Photocatalyst for Visible‐Light‐Driven Overall Water Splitting (Adv. Theory Simul. 4/2019). Issue 4 (4th April 2019) - Wan, Qiang; Wei, Fenfei; Ma, Zuju; Anpo, Masakazu; Lin, Sen
Abstract : Porous h ‐BN ( p ‐BN) as metal‐free 2D photocatalyst for visible‐light‐driven overall water splitting is demonstrated by Zuju Ma, Sen Lin, and co‐workers in article number1800174 . Carbon doping shifts the valence band maximum of p ‐BN to be energetically favorable for the oxygen evolution reaction. This work helps the design of promising 2D photocatalysts that avoid the use of metals.